Mapping the development of a new MA programme in higher education: comparing privately held perceptions of a public endeavour. Issue 2 (4th March 2017) - Kinchin, Ian; Hosein, Anesa; Medland, Emma; Lygo-Baker, Simon; Warburton, Steven; Gash, Darren; Rees, Roger; Loughlin, Colin; Woods, Rick; Price, Shirley; Usherwood, Simon
Abstract: After spending a year working on the development of a new online Master's programme in higher education, members of the development team were interviewed to reveal their thoughts about the nature of the programme. The dialogue of each interview was summarised as a concept map. Analysis of the resulting maps included a modified Bernsteinian analysis of the focus of the concepts included in terms of their semantic gravity (i.e. closeness to context) and the degree of resonance with the underpinning regulative discourse of the programme. Data highlight a number of potential issues for programme delivery that centre around the use of appropriate language to manage student expectations in relation to the process of learning and the emotional responses this can stimulate, as well as the tensions that can be foregrounded between the demands of teaching and research within a university environment.